DNA Isolation: A Method for Improving the Efficiency of DNA Extraction from Clotted Blood Samples - Bobby Rianto Adi Putra (HM Publisher, 2021)
In general, the genome research of high DNA extraction from clotted blood produced a low quality. The aim of this study is to develop a simple and safe technique for dispersing blood clots with ball-bearing metal shots. A total of 31 clotted blood samples were randomly selected as part of the Mashhad Stroke and Heart Atherosclerotic Disorders (MASHAD) study. Ten milliliters of peripheral blood were collected in plain tubes. Samples were spun, and the serum was separated. All tubes containing clotted blood were stored at −80°C. Another 32 samples of clotted blood from this cohort were chosen and considered as a comparator group. The yield and purity of DNA obtained by the three steps were significantly different (P < 0.0001), with a higher yield in the modified salting-out method. In conclusion, the salting-out method is simple, efficient, and economical for DNA isolation from old clotted blood samples.